The efficacy of oral appliances treatment for obstructive sleep apnea - Geraldine Ria Adrianne; Ira Tanti (Indonesian Journal of Prosthodontic, 2023)
Obstructive sleep apnea (OSA) is a sleep disorder caused by upper airway obstruction. There are about one bil-lion people worldwide affected by OSA; in the past decade, the number of people who seek treatment for OSA is increasing. Although continuous positive airway pressure (CPAP) is the gold standard for OSA treatment, the dentist also has a role in treating OSA using oral appliances (OA), especially for those who do not want to be treated using CPAP. However, the efficacy of OA treatment for OSA is varied so further study is needed. This sco-ping review ia aimed to evaluate the efficacy of OA treatment for OSA on adult patients with different severity based on the apnea-hypopnea index (AHI) which is classified as a mild, moderate, and severe group. It is con-cluded that OA effectively reduces the symptoms of OSA. It must be noted that objective examination through the AHI evaluation shows that AHI reduction is affected based on the OSA and BMI classification. Patients with high BMI demonstrated a smaller reduction in AHI, thus showing low effectiveness of OA.